Pengembangan Kapasitas Lembaga (Strategi dan Kebijakan untuk Peningkatan Kualitas Sistem Layanan dan Kelembagaan) - Chairul Anwar; Zaenab Hanim (Journal on Education, 2025)
Institutional capacity building is a crucial aspect in increasing the effectiveness of organizations and public services. However, various factors such as limited human resources, budget, and suboptimal policy support are often obstacles in the process of strengthening institutional capacity. Therefore, an appropriate development strategy is needed to ensure institutional sustainability and effectiveness. This study uses a literature review method by analyzing various empirical studies from accredited journals in the last five years. The analysis focuses on policy effectiveness, inhibiting factors, success indicators, best development models, and the long-term impact of strengthening institutional capacity. The results of the literature review show that the effectiveness of capacity building policies is greatly influenced by careful planning, regulatory support, and adequate resource allocation. The main inhibiting factors include limited human resources, budget, and organizational culture that is less adaptive. Success indicators can be measured through improving human resource competence, policy effectiveness, quality of public services, and collaboration between stakeholders. The best models in capacity building include the Capacity Development Model, Learning Organization, and Collaborative Capacity Building, which emphasize aspects of institutional innovation and strengthening work networks. Institutional capacity building has a long-term impact on improving organizational performance and institutional resilience in the face of challenges. Therefore, capacity building strategies must be holistic and adaptive to environmental changes in order to achieve optimal sustainability and competitiveness.